The Fatigue of the Shari‘a - Ahmad, A. author. aut Link
XIII, 208 p. 2 illus.
Keywords: The Fatigue of the Shari'a places on a continuum two kinds of debates: debates in the Islamic tradition about the end of access to divine guidance and debates in modern scholarship in Islamic legal studies about the end of the Shari'a. The resulting continuum covers what access to divine guidance means and how it relates to Shari'a.